PENERAPAN MODEL PEMBELAJARAN KOOPERATIF SNOWBALL THROWING UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA KELAS X DALAM PEMBELAJARAN DASAR – DASAR PROGRAM KEAHLIAN AKUNTANSI DI SMK PGRI 2 TUBAN TAHUN PELAJARAN 2022/2023 - IROH, TAFRIKHATUN NADIIROH; Rochmawati, Niniek Widya (Prosiding SNasPPM, 2023)
Abstract The purpose of this study was to describe 1) Increasing student motivation and learning outcomes towards the application of the snowball throw cooperative learning model to class X students in learning the basics of the accounting expertise program. 2) Increasing motivation and learning outcomes before and after participating in the application of the snowball throw cooperative learning model to increasing motivation and learning outcomes of class X students in learning the basics of the accounting expertise program. 3) Student responses to the application of the Snowball Throwing cooperative learning model to increase student motivation and learning outcomes. This study uses a class action research design. This research was conducted in three cycles referring to classroom action research procedures, namely: action planning, action implementation, observation, and reflection. Research data were collected through several instruments: interview guide instruments, observation sheets, written tests, questionnaires and documentation. The subjects of this study were class X students at SMK PGRI 2 Tuban in the academic year 2022/2023, totaling 25 students. The results of the study obtained motivation, namely student learning after the implementation of the snowball throw cooperative learning model experienced an increase in each cycle. In cycle I, the proportion of students' learning motivation was 56% in the moderately motivated category, and increased, in cycle II, the proportion of 80% was in the highly motivated category, and in cycle III, the proportion was 94%, in the category highly motivated. Furthermore, student learning outcomes through the post test scores of cycle I, the proportion of student learning outcomes was 64% in the good category, and increased, in cycle II with the proportion of 84% in the very good category and in cycle III with the proportion of 96% in the very good category. The results of this study indicate that the cooperative learning model of throwing snowballs has increased. Keywords: Learning; Cooperative learning model throwing snowballs; Motivation; Student learning outcomes